MANAJEMEN TALENTA ASN SEBAGAI STRATEGI REFORMASI BIROKRASI UNTUK MENINGKATKAN EFISIENSI LAYANAN PUBLIK - Fanila Kasmita Kusuma (LPSDI Bina Patria, 2024)
Bureaucratic reform in Indonesia requires improving the quality of the State Civil Apparatus (ASN) to deliver public services that are efficient, adaptive, and responsive. One effective strategy is talent management, a systematic process for identifying, developing, and retaining employees with superior competencies and potential. This study aims to analyze the role of talent management as a bureaucratic reform strategy to improve public service efficiency. The research employed a qualitative approach with a case study in government institutions that have implemented a merit-based talent management system. Data were collected through in-depth interviews, document reviews, and observations, and analyzed using thematic analysis techniques. The findings reveal that implementing talent management accelerates service processes, increases public satisfaction, and minimizes resource waste by placing employees in positions that align with their competencies and potential. Successful implementation is influenced by regulatory support, leadership commitment, technological infrastructure, and an adaptive work culture. These findings emphasize that talent management is not only relevant as a strategy for developing public sector human resources but also as a strategic instrument to drive successful bureaucratic reform for high-performing public services